Brucella-associated hemophagocytic syndrome: case report of a potentially life-threatening condition and literature review - Shi, Limei; Wang, Bin; Peng, Danping; Zhang, KaiYu; Wang, Yang (Frontiers in Immunology, 2025)
Brucellosis is a highly contagious zoonotic disease characterized by a non-specific clinical presentation and complex disease progression and outcome. Hemophagocytic lymphohistiocytosis (HLH) is an abnormal immune response syndrome marked by potentially fatal cytokine storms. Brucella-associated HLH is exceedingly rare and associated with a high mortality rate. We report a case involving a 23-year-old male residing in a brucellosis-endemic region, with a documented history of exposure to cattle and sheep. He was admitted to the hospital presenting with fever and arthralgia. Laboratory tests indicated splenomegaly, pancytopenia, elevated serum aminotransferases and ferritin levels, as well as decreased fibrinogen levels. Blood and bone marrow cultures yielded negative results. The Brucella serum agglutination test returned a positive result (titer, 1:200). Bone marrow aspirate results revealed an increased number of hemophagocytes, and PET-CT scans demonstrated splenomegaly, suggesting hemophagocytic changes. Following a comprehensive exclusion of hematological malignancies and neoplastic diseases, the patient was diagnosed with probable Brucella infection complicated by secondary HLH. Standard anti-brucellosis therapy was initiated immediately upon hospital admission. Remarkably, significant clinical improvement was observed within 7 days of targeted antibiotic treatment, without the need for corticosteroid therapy. This case, when analyzed alongside a systematic review of 12 published HLH cases associated with brucellosis, underscores the importance of maintaining a heightened clinical suspicion for this life-threatening complication in endemic regions, which may facilitate earlier diagnosis and optimized antimicrobial management strategies.